Simulating ultrasonic sensing with the lattice gas model. - McKerrow, P.J (IEEE Transactions on robotics and automation)
People have difficulty understanding ultrasonic sensing because they cannot see sound. The purpose of simulation is to overcome this problem by visualizing the scattering of ultrasonic waves off objects. The lattice gas model calculates wave behavior with finite difference equations to produce data suitable for grayscale visualization. This visualization is useful when designing ultrasonic sensing systems for navigating mobile robots. Situations that result in the sensor failing to detect an object can be studied with the simulator